The contributions of the use of pencil and paper for the teaching and learning of geometry in high school (Research, Society and Development, 2022)
This article is an excerpt from the master's research entitled "From pencil and paper to augmented reality: a proposal for teaching geometric visualization", which aims to analyze the possible contributions of a proposal for teaching geometric visualization based on mathematical and scientific research. using different teaching resources. Here, we analyze the contributions of activities developed only with pencil and paper for the teaching and learning of geometry. Participated in this research 16 students from the 3rd grade of high school, living in Guaçuí - ES. The use of this resource aroused little interest among students. Material limitations (2D representation of 3D objects) made it difficult, for example, to observe intersections between figures. The activity allowed contemplating the following skills: figure-ground perception; mental rotation and visual discrimination. The following skills were not covered: perceptive constancy; perception of spatial positions and perception of spatial relationships. Finally, activities with pencil and paper have the following advantages: they are easy to perform; stimulate students' creativity and help to develop students' drawing skills. We conclude that the use of a simple resource, such as pencil and paper, can contribute to the development of important skills in students.